CYP2C9 variants as a risk modifier of NSAID-related gastrointestinal bleeding: a case–control study. Issue 2 (February 2016) - Figueiras, Adolfo; Estany-Gestal, Ana; Aguirre, Carmelo; Ruiz, Borja; Vidal, Xavier; Carvajal, Alfonso; Salado, Inés; Salgado-Barreira, Angel; Rodella, Luca; Moretti, Ugo; Ibáñez, Luisa
Abstract : Objective: The aim of this study was to assess whether the CYP2C9*2 and/or *3 variants might modify the risk for NSAID-related upper gastrointestinal bleeding (UGIB) in NSAID users. Patients and methods: We conducted a multicenter, case–control study in which cases were patients aged more than 18 years with a diagnosis of UGIB, and controls were matched (1 : 3) by sex, age, date of admission, and hospital. Exposure was defined as the mean number of defined daily doses (DDDs) of NSAIDs metabolized by CYP2C9 in the week preceding the index date. Three DDD categories were defined (0, ⩽0.5, and >0.5). Exposure was constructed taking both NSAID use and CYP2C9 polymorphisms into account. Patients of non-European origin were excluded from the analysis. Results: A total of 577 cases and 1343 controls were finally included in the analysis: 103 cases and 89 controls consumed NSAIDs metabolized by CYP2C9, and 88 cases and 177 controls were CYP2C9*3 carriers. The adjusted odds ratios (aORs) of UGIB associated with the CYP2C9*2 and wild-type alleles proved to be similar [OR=8.79 (4.50–17.17) and 10.15 (2.92–35.35), respectively] and lower than those of the CYP2C9*3 allele [aOR=18.07 (6.34–51.53)] for consumers taking more than 0.5 DDDs of NSAIDs metabolized by CYP2C9. Grouping genotypes into carriers and noncarriers of the CYP2C9*3 variant resulted in aORs of 16.92 (4.96–57.59) for carriers and 9.72 (4.55–20.76) for noncarriers, where DDDs were greater than 0.5. Conclusion: The presence of the CYP2C9*3 variant increases the risk for UGIB associated with NSAID for DDDs greater than 0.5. The presence of the CYP2C9*2 allele shows no such effect.